2021
DOI: 10.1007/s00421-021-04681-w
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral autoregulation assessed by near-infrared spectroscopy: validation using transcranial Doppler in patients with controlled hypertension, cognitive impairment and controls

Abstract: Purpose Cerebral autoregulation (CA) aims to attenuate the effects of blood pressure variation on cerebral blood flow. This study assessed the criterion validity of CA derived from near-infrared spectroscopy (NIRS) as an alternative for Transcranial Doppler (TCD). Methods Measurements of continuous blood pressure (BP), oxygenated hemoglobin (O2Hb) using NIRS and cerebral blood flow velocity (CBFV) using TCD (gold standard) were performed in 82 controls, 27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Cerebral perfusion is influenced by cerebral autoregulation (aiming to attenuate cerebral blood flow and cerebral oxygenation fluctuations during orthostatic BP drops) and may for clinical purposes be derived from near-infrared spectroscopy (NIRS) measurements. NIRS measurements reflect changes of cerebral oxygenated and deoxygenated hemoglobin concentrations in the brain, and are less dependent on operator training and temporal bone anatomy compared to transcranial Doppler measurements (Mol et al, 2020b;Mol et al, 2019a;Kainerstorfer et al, 2015;Mol et al, 2021). Orthostatic cerebral oxygenation changes measured with NIRS may depend on age, sex, type of postural change (i.e., standing up from sitting versus supine position), BP and baroreflex sensitivity (BRS, defined as change in inter beat interval divided by change in BP) (Mol et al, 2020b;Mol et al, 2018b;Mol et al, 2020a;Tzeng et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Cerebral perfusion is influenced by cerebral autoregulation (aiming to attenuate cerebral blood flow and cerebral oxygenation fluctuations during orthostatic BP drops) and may for clinical purposes be derived from near-infrared spectroscopy (NIRS) measurements. NIRS measurements reflect changes of cerebral oxygenated and deoxygenated hemoglobin concentrations in the brain, and are less dependent on operator training and temporal bone anatomy compared to transcranial Doppler measurements (Mol et al, 2020b;Mol et al, 2019a;Kainerstorfer et al, 2015;Mol et al, 2021). Orthostatic cerebral oxygenation changes measured with NIRS may depend on age, sex, type of postural change (i.e., standing up from sitting versus supine position), BP and baroreflex sensitivity (BRS, defined as change in inter beat interval divided by change in BP) (Mol et al, 2020b;Mol et al, 2018b;Mol et al, 2020a;Tzeng et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A NIRS model using a slightly different HF-range correction for serial time trends was previously studied in awake patients with (mild) cognitive and in healthy subjects. They studied the relationship between ABP and oxyHb [ 24 ]. It might be interesting to compare our results with those retrieved from ABP—oxyHb calculations.…”
Section: Discussionmentioning
confidence: 99%
“…6 Numerous investigations evaluating neck vasculature in patients with diabetes, hypertension, and coronary artery disease utilizing CAU and TCD have demonstrated good sensitivity and specificity in disease prediction. [7][8][9][10] Studies have revealed that TCD has an 88% specificity and a 91% sensitivity for the diagnosis of ischemic stroke. 11 Therefore, the use of CAU and TCD for the detection of vascular function in the neck can lead to early detection of vascular dysfunction, which can lead to interventional treatment and reduce the possibility of serious disease.…”
Section: Introductionmentioning
confidence: 99%